Socio-economic factors influencing poverty among rural households in onicha local government area, ebonyi state, Nigeria (International Journal of Agricultural Research, Innovation and Technology, 2019)
The study examined the socio-economic factors influencing poverty among rural households in Onicha Local Government Area of Ebonyi state, Nigeria. The study adopted multistage random and purposive sampling techniques to select 120 household heads. Primary data used for the study were collected using structured questionnaire. The data were analysed with the aid of means, percentage and frequency count and OLS multiple regression model. The result indicated that the households spent an average of N31,250 monthly to take care of their families and other essential personal needs. The result of the socio-economic characteristics showed that majority (53.3) of the respondents were females. The mean age was 36 years with majority (64.2%) married while an average of 6 persons per household was recorded. The predominant occupations were farming (36.0%) and civil service (35.8%). The households cultivated a mean farm size of 3.8 hectares, the mean monthly income was N19,720 while their average monthly expenditure amounted to N31,250. Moreover, 73.3% of the respondents belonged to one social organization or the other with over 90.0% of them having acquired various forms of formal education. The multiple regression result showed the coefficient of determination (R2) was 0.644 or 64.4%. The overall model was statistically significant (P